Temporal Dynamics and Ecological Process - Kelly, Colleen K.; Bowler, Michael G.; Fox, Gordon A. (Cambridge : Cambridge University Press, 2013)
In contrast with the fundamental ecological expectation that similarity induces competition and loss of species, temporal dynamics allows similar species to co-occur. In fact, the coexistence of similar species contributes significantly to species diversity and could affect ecosystem response to climate change. However, because temporal processes take place over time, they have often been a challenge to document or even to identify. Temporal Dynamics and Ecological Process brings together studies that have met this challenge and present two specific aspects of temporal processes: reproductive scheduling and the stable coexistence of similar species. By using plants to extract general principles, these studies uncover deep ties between temporal niche dynamics and the above central ecological issues, thereby providing a better understanding of what drives temporal processes in nature. Written by leading scientists in the field, this title will be a valuable source of reference to research ecologists and those interested in temporal ecology.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Population biology; Biotic communities; Plant populations